Can an inadequate cervical cytology sample in ThinPrep be converted to a satisfactory sample by processing it with a SurePath preparation? - Sørbye, Sveinung; Pedersen, Mette Kristin; Ekeberg, Bente; Wiliams, Merete E. Johansen; Sauer, Torill; Chen, Ying (Medknow Publications, 2017)
Published version available in http://doi.org/10.4103/cytojournal.cytojournal_34_16 . Background: The Norwegian Cervical Cancer Screening Program recommends screening every 3 years for women between 25 and 69 years of age. There is a large difference in the percentage of unsatisfactory samples between laboratories that use different brands of liquid-based cytology. We wished to examine if inadequate ThinPrep samples could be satisfactory by processing them with the SurePath protocol. Materials and Methods: A total of 187 inadequate ThinPrep specimens from the Department of Clinical Pathology at University Hospital of North Norway were sent to Akershus University Hospital for conversion to SurePath medium. Ninety-one (48.7%) were processed through the automated “gynecologic” application for cervix cytology samples, and 96 (51.3%) were processed with the “nongynecological” automatic program. Results: Out of 187 samples that had been unsatisfactory by ThinPrep, 93 (49.7%) were satisfactory after being converted to SurePath. The rate of satisfactory cytology was 36.6% and 62.5% for samples run through the “gynecology” program and “nongynecology” program, respectively. Of the 93 samples that became satisfactory after conversion from ThinPrep to SurePath, 80 (86.0%) were screened as normal while 13 samples (14.0%) were given an abnormal diagnosis, which included 5 atypical squamous cells of undetermined significance, 5 low-grade squamous intraepithelial lesion, 2 atypical glandular cells not otherwise specified, and 1 atypical squamous cells cannot exclude high-grade squamous intraepithelial lesion. A total of 2.1% (4/187) of the women got a diagnosis of cervical intraepithelial neoplasia 2 or higher at a later follow-up. Conclusions: Converting cytology samples from ThinPrep to SurePath processing can reduce the number of unsatisfactory samples. The samples should be run through the “nongynecology” program to ensure an adequate number of cells.